(untitled) (TSUL LEGAL REPORT, 2026)
The study is devoted to the legal nature and theoretical justification of the concept of terrorism financing, which is considered as an independent crime that emerged as a result of the development of international and national anti-terrorism legislation. The paper analyzes the subject and topic of the research by establishing the connection between terrorism, crimes of a terrorist nature, and the financial mechanisms that ensure their commission. The aim of the research is to identify problems related to the legal definition of terrorism financing and to substantiate the need for its normative improvement. The relevance of the study is determined by the absence of a unified approach in legislation and doctrine, which complicates law-enforcement practice and the identification of this act. The methodological basis consists of comparative-legal, systemic, and formal-legal methods. As a result, significant differences between international and national definitions of terrorism and terrorism financing were identified, demonstrating the incompleteness of current formulations and the need for an expanded interpretation. The practical significance lies in the possibility of applying the proposed conclusions to improve criminal legislation and mechanisms for combating terrorism financing. It is concluded that clarifying the normative definition, taking into account international standards, and incorporating the category of crimes of a terrorist nature into legal regulation are essential for the proper qualification of terrorism financing.